The yearly rate of Relative Thalamic Atrophy (yrRTA): a simple 2D/3D method for estimating deep gray matter atrophy in Multiple Sclerosis - Menéndez-González, Manuel; Salas-Pacheco, José M.; Arias-Carrión, Oscar (Frontiers in Aging Neuroscience, 2014)
Despite a strong correlation to outcome, the measurement of gray matter (GM) atrophy is not being used in daily clinical practice as a prognostic factor and monitor the effect of treatments in Multiple Sclerosis (MS). This is mainly because the volumetric methods available to date are sophisticated and difficult to implement for routine use in most hospitals. In addition, the meaning of raw results from volumetric studies on regions of interest are not always easy to understand. Thus, there is a huge need of a methodology suitable to be applied in daily clinical practice in order to estimate GM atrophy in a convenient and comprehensive way. Given the thalamus is the brain structure found to be more consistently implied in MS both in terms of extent of atrophy and in terms of prognostic value, we propose a solution based in this structure. In particular, we propose to compare the extent of thalamus atrophy (TA) with the extent of unspecific, global brain atrophy, represented by ventricular enlargement. We name this ratio the “yearly rate of Relative Thalamic Atrophy” (yrRTA). In this report we aim to describe the concept of yrRTA and the guidelines for computing it under 2D and 3D approaches and explain the rationale behind this method. We have also conducted a very short crossectional retrospective study to proof the concept of yrRTA. However, we do not seek to describe here the validity of this parameter since these researches are being conducted currently and results will be addressed in future publications.